Japan in the world economy - Balassa, Bela A.; Noland, Marcus; Institute for International Economics (U.S.) (Washington, DC : Institute for International Economics, 1988)
The study is the product of the Institute's continuing research on Japan and its participation in the world economy. The book's focus on Japan's global role provides a complement to the bilateral theme of "The United State - Japan Economic Problem", by William R. Cline and the author, which was originally released by the Institute in October 1985 and in revised form in January 1987. This new volume provides an in-depth analysis of several of the key structural features of the Japanese economy that were cited in the Bergsten-Cline study but could not be adequately addressed there.
Includes index.
Bibliography: p. 269-280.
rpm 16/11/2017
Loans
Keywords: Saving and investment; Economic assistance, Japanese; Japan; Japan